Designing a model of effective marketing capabilities based on communication - Yoones Banisaeed; Ghanbar Amirnejad; Morteza mousakhani; Leila Andervazh (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of the current research is to design a model of effective marketing capabilities based on communication (case study: National Drilling Company). The research method is applicable in terms of its purpose; mixed (qualitative-quantitative) in terms of execution method; descriptive-survey in terms of nature and method; and it is an exploratory study type of research. The statistical population of the research includes 10 experts, professors and strategic managers of National Iranian Drilling Company. Data collection in the qualitative part was carried out through semi-structured interviews, and in the quantitative part by the questionnaire. Coding was used in the data analysis of the qualitative part, and SPSS and Lisrel software were used in the quantitative part. The results of the research showed that after core and optional coding and creation of main and sub-categories, six dimensions of effective marketing capabilities based on communication were identified, i.e. strategic capabilities, operational capabilities, functional capabilities, internal capabilities of the company, and external capabilities and communication as dimensions of effective marketing capability methods based on communication. Extended Abstract Introduction Today, with the expansion of the globalization process, the increase in competition, the entry of various domestic and foreign companies, various products and the advancement of technology, it is difficult to maintain customer satisfaction and loyalty; therefore, it seems necessary to take advantage of marketing capabilities and strategies to survive in the competitive scene; because these two factors can provide a good foundation for improving the business performance of the company (Asgarnezhad Nouri et al, 2020). Both areas of marketing capabilities are very important and vital to achieve business success. Marketing capabilities are defined as the organizational ability to perform a set of tasks and affairs by using existing organizational resources to achieve the desired performance result (Herhausen et al, 2020). According to Guo et al, (2018), marketing capabilities improve an organization's ability to configure and effectively implement resources to create a sustainable competitive advantage. Therefore, marketing capabilities are a complex combination of organizational capabilities and resources, unique to an organization and difficult to be imitated by other organizations (Karamipur, 2023). In recent studies, marketing capabilities have been defined as the process of applying knowledge, skills, and organization resources to create added value for goods and services, meet competitive demands, and respond to market-related needs (Orak & Babaeezakilaki, 2015). The importance of learning processes in the development of marketing capabilities has been emphasized, especially when employees can quickly solve the company's marketing problems using their knowledge and skills. Marketing assets and capabilities are the foundation of business units; and customer relationship, production or promotion, and customer orientation are based on knowledge and process (Emami et al, 2022). Therefore, this research seeks to answer the question: What is the model of effective marketing capabilities based on communication? Theoretical framework Marketing ability Marketing capability is an integrated process in which companies use tangible and intangible resources to understand the complexity of specific customer needs, achieve relative differentiation in products for competitive advantage, and finally achieve appropriate quality. Marketing capabilities are integrated and coherent processes designed to apply the company's collective skills, knowledge and resources; and improve the value of the company's goods and services, and by means of these capabilities; the company is able to adapt to changing market conditions and use market opportunities to deal with competitive threats. Marketing capability indicates a company's specific abilities in identifying target markets, strategies and developing market mixes that maintain relationships with loyal customers (Zahiri et al, 2016). Aripin et al, (2024) investigated marketing capability and market ambiguity on the results of product innovation. They stated that strategies and best practices such as in-depth market research, cross-collaboration, leveraging technology and data analytics, forming strategic partnerships and a strong innovation culture are essential. In-depth market research helps companies understand customer needs and preferences as well as emerging market trends, while cross-collaboration allows them to maximize internal knowledge and expertise. The use of technology and data analytics helps companies to collect and analyze market data more effectively, while the formation of strategic partnerships gives them access to additional resources and knowledge. Finally, a strong innovation culture is an important foundation for creating an environment that supports sustainable product innovation. By implementing these strategies, companies can improve their ability to generate relevant and sustainable product innovations and thus remain competitive in an increasingly complex market. Karamipur (2023) investigated the design of the model of artificial intelligence competencies on organizational performance by considering business-to-business marketing capabilities. The results showed that the mechanisms of artificial intelligence competencies have an effect on business-to-business marketing capabilities and organizational performance, and also the model of artificial intelligence competencies on organizational performance is confirmed by considering the aspect of business-to-business marketing capabilities. Research methodology The research method is applicable in terms of its purpose; mixed (qualitative-quantitative) in terms of execution method; descriptive-survey in terms of nature and method; and it is an exploratory study type of research. The statistical population of the research includes 10 experts, professors and strategic managers of National Iranian Drilling Company. Data collection in the qualitative part was carried out through semi-structured interviews, and in the quantitative part by the questionnaire. Research findings Coding was used in the data analysis of the qualitative part, and SPSS and Lisrel software were used in the quantitative part. The results of the research showed that after core and optional coding and creation of main and sub-categories; six dimensions of effective marketing capabilities based on communication were identified, i.e. strategic capabilities, operational capabilities, functional capabilities, internal capabilities of the company and external capabilities and communication as dimensions of capability of effective communication-based marketing strategies, therefore it was suggested that intangible resource planning and marketing planning be done based on marketing strategies, and strengthening and increasing human resources skills and human capital in the target markets be carried out. Conclusion The present research was conducted with the aim of designing a model of effective marketing capabilities based on communication (case study: National Drilling Company). The results of this research are in agreement with the results of Aripin et al, (2024), Karamipur (2023), Doah et al, (2023), Khodabakhshi & Melai (2023), Oduro & Williams (2023), Afsharfar (2022), Rajabi (2020), Takata (2016), Nasimi & Amiri (2018). Doah et al, (2023) showed that elucidating the underlying mechanisms through which marketing capability affects firm performance contributes to the growing body of knowledge about marketing strategy. In practice, this study provides strategic insights for companies that increase their marketing effectiveness and overall performance by optimizing their resource management capabilities. The implications of this research extend to marketing practitioners, strategists, and researchers seeking a deeper understanding of the nuanced interplay between marketing capabilities, resource coordination, and firm performance in the contemporary business landscape. The results showed that resource coordination capability has a positive relationship with marketing capabilities, and an inverse relationship was obtained between company performance and resource coordination capabilities. According to the results of this research, the following suggestions are presented: Intangible resource planning and marketing planning can be done based on marketing strategies. Planning channels be designed and reach the implementation stage according to the target markets Customer access should be done according to the conditions, external knowledge ability, customer knowledge, customer connection capability, technical knowledge, strengthening and increasing the skills of human resources and human capital in the target markets. Public relations, as the heart and lifeblood of the company, should be managed by using experienced personnel with technical communication skills.